2007
DOI: 10.1007/s00268-007-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Accelerates the Recovery from Burn Wounds

Abstract: A full-thickness burn wound model was used to evaluate the effects of a topically applied gel-based nitric oxide donor on wound healing in rats. The histological study demonstrated that the nitric oxide (NO) application significantly promoted re-epithelization that resulted in a fast recovery of burn wound. The histological sections further revealed that inflammatory cell infiltration in the NO-treated group was significantly increased in comparison to the control group. The enhanced accumulation of inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 32 publications
3
70
1
1
Order By: Relevance
“…[1,2,[34][35][36] However, to the best of our knowledge, the use of POMs as a carrier for NO storage and delivery has never been reported. Fortunately, according to our previous ESI-MS study [37] on organoimido derivatives of POMs, these compounds are unstable in nearly neutral or basic aqueous solutions.…”
Section: No Release Studymentioning
confidence: 90%
“…[1,2,[34][35][36] However, to the best of our knowledge, the use of POMs as a carrier for NO storage and delivery has never been reported. Fortunately, according to our previous ESI-MS study [37] on organoimido derivatives of POMs, these compounds are unstable in nearly neutral or basic aqueous solutions.…”
Section: No Release Studymentioning
confidence: 90%
“…Previous reports have indicated that nitric oxide influences cytokines, chemokines, and the infiltration of inflammatory cells to the burn wound [18]. Nitrate/nitrite is a metabolite of NO, and in our previous study in nonburn mice, we found that midazolam significantly attenuated the LPS-induced increase in serum nitrate [8].…”
Section: Midazolam Increased Serum Nitratementioning
confidence: 92%
“…8). A major source of the serum nitrate/nitrite following burn injury reportedly is from the burn wound [18]. We performed real-time RT-PCR to ascertain the mRNA levels of eNOS and iNOS because these are the rate limiting enzymes in the production of NO.…”
Section: Midazolam Increased Serum Nitratementioning
confidence: 99%
“…6 Indeed, it mediates a number of vital functions, including vasodilatation 7 and re-epithelization. 8 The accumulation of high concentrations of nitric oxide in tumours offers the possibility to increase cancer cells' sensitivity to chemoand radiotherapy or even to suddenly induce their apoptosis. 9 Remarkably, recent studies described the use of NO to enhance cisplatin cytotoxicity in V79 lung fibroblast cells taking advantage from the direct sensitizing of tumour cells.…”
mentioning
confidence: 99%